2008
DOI: 10.1007/s00208-008-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

An extension of the Weil–Petersson metric to quasi-Fuchsian space

Abstract: We define a natural semi-definite metric on quasi-fuchsian space, derived from geodesic current length functions and Hausdorff dimension, that extends the Weil-Petersson metric on Teichmüller space. We use this to describe a metric on Teichmüller space obtained by taking the second derivative of Hausdorff dimension and show that this metric is bounded below by the Weil-Petersson metric. We relate the change in Hausdorff dimension under bending along a measured lamination to the length in the Weil-Petersson met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…which is sharpened by Theorem 1.1, and include an inequality version of Corollary 1.2 [BT2,§11]. We remark that the pseudometric on quasifuchsian space introduced in [BT2] can also be regarded as a pullback of the pressure metric.…”
Section: Thermodynamicsmentioning
confidence: 95%
See 1 more Smart Citation
“…which is sharpened by Theorem 1.1, and include an inequality version of Corollary 1.2 [BT2,§11]. We remark that the pseudometric on quasifuchsian space introduced in [BT2] can also be regarded as a pullback of the pressure metric.…”
Section: Thermodynamicsmentioning
confidence: 95%
“…We remark that the pseudometric on quasifuchsian space introduced in [BT2] can also be regarded as a pullback of the pressure metric. I would also like to thank M. Zinsmeister and the referees for many useful comments.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…Burger [9] introduced a renormalized pressure intersection between convex cocompact representations into rank one Lie groups. Bridgeman and Taylor [7] extensively studied this renormalized pressure intersection in the setting of quasifuchsian representation. We say that ρ : π 1 (S) → PSL(2, C) is quasifuchsian if it is topologically conjugate, in terms of its action on C, to a Fuchsian representation into PSL(2, R).…”
Section: 3mentioning
confidence: 99%
“…Bridgeman and Taylor [7] showed that the Hessian of J gives rise to a non-negative bilinear form on the tangent spaceTQF (S) of quasifuchsian space, called the pressure form. Motivated by work of McMullen [24] in the setting of Teichmüller space, Bridgeman [5] used the thermodynamic formalism to show that the only degenerate vectors for the pressure form correspond to pure bending at points on the Fuchsian locus.…”
Section: 3mentioning
confidence: 99%
“…Bridgeman and Taylor [18] used Patterson-Sullivan theory to show that the Hessian of the renormalized intersection number is a non-negative form on quasifuchsian case. McMullen [62] then introduced the use of the techniques of Thermodynamic Formalism to interpret both of these metrics as pullbacks of the pressure metric on the space of suspension flows on the shift space associated to the Bowen-Series coding.…”
Section: Basic Strategymentioning
confidence: 99%